1993
DOI: 10.1177/00220345930720021101
|View full text |Cite
|
Sign up to set email alerts
|

Caries Risk Assessment in a Longitudinal Discrimination Study

Abstract: Our objective was to develop and perfect a model for the assessment of risk of dental caries onset in children. Even though dental caries prevalence in children is continuing to decline, there is still a significant minority for whom it is a problem. In this study, we sought to ascertain whether a set of variables selected in a previous cross-sectional study could be used to differentiate between caries-free six-year-olds who would or would not subsequently present with clinically-detectable caries. A total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(71 citation statements)
references
References 10 publications
2
67
0
2
Order By: Relevance
“…Unfortunately, there is no simple, valid, and reliable caries risk assessment model currently available. Previous caries experience and/or untreated (active) lesions are the best predictors for future caries development [Bibby and Shern, 1978;Disney et al, 1992;Leverett et al, 1993;Hausen et al, 1994;Vanobbergen et al, 2001;Featherstone et al, 2003]. However, these predictors are post-disease and do not serve well for early detection and primary prevention of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, there is no simple, valid, and reliable caries risk assessment model currently available. Previous caries experience and/or untreated (active) lesions are the best predictors for future caries development [Bibby and Shern, 1978;Disney et al, 1992;Leverett et al, 1993;Hausen et al, 1994;Vanobbergen et al, 2001;Featherstone et al, 2003]. However, these predictors are post-disease and do not serve well for early detection and primary prevention of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Also, Kawasaki et al [2000] showed an effect of fluoride on remineralization of shallow (!165 Ìm) dentinal lesions with various mineral distributions. With an in situ model Nyvad et al [1997] showed -in comparison with non-treatment -that daily plaque removal and application of 2% NaF could inhibit progression and even result in partial remineralization of dentinal lesions Intra-oral fluoride levels between 0.04 and 0.1 ppm may be found in saliva and plaque fluid when a fluoride toothpaste or rinse is being used [Duckworth and Morgan, 1991;Leverett et al, 1993]. Fluoride levels in the subparts per million range have been shown to shift the deremineralization balance significantly in vitro [Jacobson et al, 1991], although it was observed that higher levels of fluoride were needed to attain a similar degree of caries prevention when compared with enamel [ten Cate, 1999].…”
Section: Discussionmentioning
confidence: 99%
“…Potentially positive risk factors and potential protective factors were combined as proposed in the scientific literature [Leverett et al, 1993]. 'Daily use of sugar containing drinks' was confirmed to be a behavioural risk factor.…”
Section: Validation Of Risk Indicatorsmentioning
confidence: 99%
“…In previously published studies a number of workers have attempted to identify high-risk individuals and groups with varying degrees of success, depending on the age group, the baseline caries experience and the caries incidence rate of the study group. Several studies use a combination of tests for caries prediction, stressing past caries experience or salivary counts [ter Pelk- , 1990;Helfenstein et al, 1991;Leverett et al, 1993]. Several other studies have examined the use of a wider range of factors in caries prediction, involving behavioural and socio-demographic factors.…”
Section: Risk Predictorsmentioning
confidence: 99%